Determining dairy producers’ willingness to pay for beef genetic attributes - McCollum, Calder (My University, 2025)
The purpose of this study was to quantify dairy producers’ willingness to pay for beef EPD attributes in the development of beef x dairy calves. A discrete choice experiment was conducted as part of a larger production survey designed to better understand beef x dairy production and marketing decisions. This production survey highlighted key marketing decisions undertaken by beef x dairy producers such as motivations for incorporation, typical marketing practices, knowledge of EPDs, and sociodemographic characteristics. The discrete choice experiment represented a hypothetical scenario for dairy producers purchasing beef genetics in a semen straw. Survey participants were given the option of three straws with differing EPD attributes and a non-purchase alternative. Respondents were required to choose one of the four options for each scenario for a total of nine choice scenarios each. Attributes included price, calving ease direct EPD, marbling EPD, and dry matter intake EPD. Results were evaluated using both a standard conditional logit and a random parameters (mixed) logit. Marginal effects on probability of choice were evaluated as well as marginal willingness to pay estimates for select genetic attributes including calving ease direct, marbling, and dry matter intake. Results reveal that dairy producers value terminal and management traits over maintenance traits. Producers are less likely to purchase straws with inferior calving ease traits and high prices. Alternatively, producers are more likely to purchase straws with superior marbling traits. Marginal willingness to pay (WTP) estimates demonstrate a strong producer WTP for superior marbling traits with positive and significant negative WTP for straws with inferior calving ease indicating that producers are wary of compromising management traits when seeking carcass benefits from a beef x dairy cross. Additionally, producer preferences across EPD attributes are revealed to be heterogeneous across calving ease and superior marbling traits.
Keywords: Dairy; Beef; Beef x Dairy; EPDs; WTP; Discrete choice